The Influence of Memory Load, Speech-to-Noise Ratio, and Stimulus Rehearsal on the Pupil Dilation Response: Implications for the Assessment of Listening Effort. - Zekveld, Adriana A.; Visser, Veerle W.; Kramer, Sophia E.; Sangers, Jorn; Smitsb, Cas (Journal of Speech, Language & Hearing Research, 2026)
Purpose: Pupillometry has been frequently used to examine the influence of auditory task demand on listening effort. However, the intelligibility effect on the pupil dilation response might be altered under high memory load. Method: We assessed the effects of signal-to-noise ratio (SNR; auditory demand), memory load, and stimulus rehearsal on the pupil dilation response. Twenty-four participants with normal hearing were included (M = 22 years, 16 women). Sequences of four or six digits were presented in stationary noise at two auditory demand levels. For either 20% or 80% of the trials, digits were rehearsed. Participants rated listening effort, task difficulty, performance, and tendency to give up. Results: Linear mixed-model analyses indicated that intelligibility was higher for four digits compared to six digits and for lower auditory demand compared to higher auditory demand. The mean pupil dilation was larger for lower auditory demand during listening. In the repetition interval, the peak and mean pupil dilations were larger for lower auditory demand compared to higher auditory demand, for six digits compared to four digits, and for 80% compared to 20% stimulus rehearsal. Subjective listening effort and task difficulty were higher for higher auditory demand than for lower auditory demand and for six digits than for four digits. A lower auditory demand also resulted in higher performance ratings and lower tendency to give up compared to higher auditory demand. Conclusions: The established decrease in the pupil dilation response with decreasing auditory demand (higher SNR) can be altered in tasks with relatively high memory demands. It is important to consider the memory demands imposed by the listening task when assessing the pupil dilation response.